The Relationship between Sexual Function - Soltan Ahmadi, zhila; Ranjbar, hadi; Kohan, mehri (Advances in Nursing & Midwifery, 2014)
Abstract Introduction: Sexual function is an integral part of human life. Chronic diseases, especially diabetes, have a significant impact on sexual performance. Since studies on women’s sexual function and its relationship to quality of life are scant, this study was conducted to determine sexual function in women with diabetes and its relationship to quality of life in attendees to the diabetes center of kerman Method and materials: This case-control study was carried out in diabetes centers of Kerman. Iran. The sample of the study consisted of 164 married women with diabetes and 170 non diabetic women in control group. Data were collected by a questionnaire which consisted of demographic information, the Sf36 quality of life questionnaire and sexual function scale. All statistical analyses were done by using SPSS, Categorical data were compared using χ 2 test, t test and Pearson coeffi cient were used for scores of quality of life and sexual function scale. Findings: Quality of life scores and sexual function in diabetic control group were lower than the control group (p <0.05). There was no significant relationship between sexual function and quality of life in the two groups. Age, duration of diabetes, BMI and education level were associated with sexual function. Conclusion: the impact of diabetes on sexual function of women’s sexual function on quality of life of diabetic patients will require further investigation. Keywords: Diabetes, Sexual Function, Quality of Life, Women REFERENCES Abu Ali R M, Al Hajeri R M, Khader Y S et al (2008) Sexual dysfunction in Jordanian diabetic women. Diabetes Care.31 (8) 1580-1. Aslan E and Fynes M (2008) Female sexual dysfunction. International Urogynecology Journal and Pelvic Floor Dysfunction. 19(2)293-305. Bahrami N, Soleimani M, Shraifnia H et al (2012)[ Female sexual satisfaction with different contraceptive methods]. Iran Journal of Nursing 25 (76) 55-63. (Persian) Bitzer J and Alder J (2009) Diabetes and female sexual health. Women’s Health.5 (6) 629-636. Elnashar A M, El-Dien Ibrahim M, El-Desoky M M, et al (2007) Female sexual dysfunction in Lower Egypt. BJOG: An International Journal of Obstetrics and Gynaecology. 114 (2) 201-6. Erol B, Tefekli A, Ozbey I et al (2002) Sexual dysfunction in type II diabetic females: a comparative study. Journal of Sex& Marital Therapy. 28 (Suppl 1) 55-62. Fourcroy J L (2006) Customs, culture, and tradition--what role do they play in a woman’s sexuality? Journa of Sexual Medicine. 3 (6) 954-9. Guay A T (2001) Sexual dysfunction in the diabetic patient. International Journal of Impotence Research. 13(Suppl 5) S47-50. Hassanin I M, Helmy Y A, Fathalla M M and Shahin A Y (2010) Prevalence and characteristics of female sexual dysfunction in a sample of women from Upper Egypt. International Journal of Gynaecology and Obstetrics. 108 (3) 219-23. Hayes R D, Dennerstein L, Bennett C M al (2008) Risk factors for female sexual dysfunction in the general population: Exploring factors associated with low sexual function and sexual distress.The Journal of Sexual Medicine. 5 (7) 1681-93. Hisasue S, Kumamoto Y, Sato Y et al (2005) Prevalence of female sexual dysfunction symptoms and its relationship to quality of life: a Japanese female cohort study. Urology. 65 (1) 143-8. Koch P B and Young E W (1988) Diabetes and female sexuality: a review of the literature. Health Care for Women International. 9 (4) 251-62. Laumann E O, Paik A and Rosen R C (1999) Sexual dysfunction in the United States: prevalence and predictors. JAMA 281 (6) 537-44. Lowenstein L, Pierce K and Pauls R (2009) Urogynecology and sexual function research. How are we doing? The Journal of Sexual Medicine. 6(1) 199-204. Montazeri A, Goshtasbi A and Vahdaninia M A S (2006)[ The short form health survey (sf-36): Translation and validation study of the Iranian version]. Payesh 5 (1) 49-56. (Persian) Oniz A, Keskinoglu P and Bezircioglu I (2007) The prevalence and causes of sexual problems among premenopausal Turkish women. The Journal of Sexual Medicine. 4 (6) 1575-81. Papaharitou S, Nakopoulou E, Kirana P et al (2005) Women’s sexual concerns: data analysis from a help-line. The Journal Sexual Medicine. 2 (5) 652-7. Raina R, Pahlajani G, Khan S et al (2007) Female sexual dysfunction: classification, pathophysiology, and management. Fertility & Sterility. 88 (5) 1273-84. Rosen R, Brown C, Heiman J et al. (2000) The Female Sexual Function Index (FSFI): a multidimensional self-report instrument for the assessment of female sexual function. Journal of Sex and Marital Therapy. 26 (2) 191-208. Shindel A W, Nelson C J, Naughton C K, et al (2008) Sexual function and quality of life in the male partner of infertile couples: prevalence and correlates of dysfunction. The Journal of Urology. 179 (3) 1056-9. Steinberg H O, Paradisi G, Cronin J, Crowde K, Hempfling A, Hook G and Baron A D (2000) Type II diabetes abrogates sex differences in endothelial function in premenopausal women. Circulation 101 (17) 2040-6. Taghavi M, Fatemi S , Abotorabi R (2009)[ Evaluation of sexual function in women with type 2 diabetes mellitus]. Iranian Journal of Lipid and Diabetes 8 (4) 357-62. (Persian) Tepavcevic D, Kostic J, Basuroski I, Stojsavljevic N, Pekmezovic T and Drulovic J (2008) The impact of sexual dysfunction on the quality of life measured by MSQoL-54 in patients with multiple sclerosis. Multiple Sclerosis. 14 (8) 1131-1136. Veronelli A, Mauri C, Zecchini B et al (2009) Sexual dysfunction is frequent in premenopausal women with diabetes, obesity, and hypothyroidism, and correlates with markers of increased cardiovascular risk. A preliminary report. The Journal of Sexual Medicine. 6 (6) 1561-8. Walsh K E and Berman J R (2004) Sexual dysfunction in the older woman: an overview of the current understanding and management. Drugs and Aging. 21 (10) 655-75. Whitehouse C R (2009) Sexuality in the older female with diabetes mellitus–A review of the literature. Urologic Nursing. 29 (1) 11-8. Yencilek F, Attar R, Erol B et al (2010) Factors affecting sexual function in premenopausal age women with type 2 diabetes: a comprehensive study. Fertility & Sterility. 94 (5) 1840-3. Ziaei-Rad M, Vahdaninia M and Montazeri A (2010) Sexual dysfunctions in patients with diabetes: a study from Iran. Reproductive Biology and Endocrinology. 8 (1) 50.